2016
DOI: 10.17992/lbl.2016.09.95
|View full text |Cite
|
Sign up to set email alerts
|

Fæðuval og næring kvenna á meðgöngu með tilliti til líkamsþyngdar

Abstract: InngangurRannsóknir síðastliðinna 20 ára, baeði meðal manna og dýra, benda til þess að umhverfi fósturs í móðurkviði geti haft umtalsverð áhrif á heilsu afkvaemisins allt fram á fullorðinsár.1 Naeringarástand fyrir og á með-göngu getur ekki aðeins haft áhrif á heilsu móðurinn-ar heldur einnig á þroska, vöxt og heilsu barnsins til skemmri og lengri tíma. [2][3][4] Mataraeði mismunandi samfélagshópa hefur verið rannsakað hérlendis undanfarin ár. 5,6 Þekkingin hefur meðal annars nýst við stefnumótun í lýðheilsumá… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 27 publications
2
8
0
Order By: Relevance
“…The intake of protein and fat in the diet slightly exceeded the recommendations. Similar results were obtained in studies by Gunnarsdottir et al [ 31 ]. It was also observed that the intake of complex carbohydrates was below the recommended level.…”
Section: Discussionsupporting
confidence: 92%
“…The intake of protein and fat in the diet slightly exceeded the recommendations. Similar results were obtained in studies by Gunnarsdottir et al [ 31 ]. It was also observed that the intake of complex carbohydrates was below the recommended level.…”
Section: Discussionsupporting
confidence: 92%
“…Action needs to be taken on public health level to attend to the matter. Despite Iceland's historically high iodine consumption, decreased fish and dairy consumption among women of reproductive age have been a concern (9,11,19). In 2009, the UIC of pregnant women in the capital region in Iceland (n = 162) was in accordance with WHO recommendations with a median value of 180 µg/L (9), compared to the median UIC of 89 µg/L in the present study.…”
Section: Discussionsupporting
confidence: 56%
“…Insufficient iodine status was observed for the first time in an Icelandic population, most likely related to a decline in fish and dairy intake. The reasons for the decrease in fish and dairy intake in Iceland (11,12,16) remain unknown. However, it could be speculated that public discussion on suggested negative health effects of dairy consumption and increased awareness of environmental aspects might have contributed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The data gathered with the frequency questions were transformed into predefined 13 dietary risk factors for inadequate diet (see Figure 1). These factors are based on the Nordic (Nordic Nutrition Recommendations, 2014) and Icelandic dietary recommendations (Embaetti landlaeknis, 2016), as well as evidence on the association between diet, nutrient intake, and the health of the mother and child (Englund-Ogge et al, 2012;Gunnarsdottir et al, 2016;Hrolfsdottir et al, 2016;Olafsdottir, Skuladottir, Thorsdottir, Hauksson, & Steingrimsdottir, 2006;Olsen et al, 2007;Renault et al, 2015;Zhu et al, 2017). Stepwise backward elimination (logistic regression) was used to identify the best combination of these factors for predicting excessive GWG.…”
Section: The Dietary Risk Scorementioning
confidence: 99%